Pelatihan Pembuatan Landing Page untuk Meningkatkan Efektivitas Pemasaran UMKM Balung Kuwuk Ngariyun di Desa Panunggalan - Juliyani, Erly; Sa'diyin, Moh; Mahendra, Ariel Rizal; Prayogi, Ajek Ranudin; Amelia , Husnia; Ihsabila , Ichta Dyna (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2025)
The Practical Work Experience (KKN) in Panunggalan Village, Bojonegoro Regency, focuses on developing digital marketing skills for Micro, Small, and Medium Enterprises (MSMEs) under the theme of "Asset Based Community Development" (ABCD). The program aims to enhance the marketing effectiveness of MSMEs through training in landing page creation using Canva. This training is designed to address key challenges faced by MSMEs, such as a lack of knowledge and skills in digital marketing and the inability to utilize social media and other digital platforms effectively. The training method includes both theory and practice, covering the fundamentals of digital marketing and techniques for creating and managing landing pages. The results of the training show significant positive impacts, including improved participants' understanding of digital marketing and their ability to create effective landing pages. MSME participants, particularly from the Balung Kuwuk cassava chip business, experienced increases in online visibility and sales conversion. In conclusion, the training successfully strengthened MSME digital marketing strategies and demonstrated substantial potential for advancing businesses through digital technology.